Effect of Addition of Seaweed (Sargassum sp) Charcoal with Pure Graphite on the Electrical Properties of Graphene Oxide Synthesized by the Modified Hummer’s Method - Ra'uf, Andhyka; Ramli, -; Gusnedi, -; Hidayat, Rahmat (PILLAR OF PHYSICS, 2024)
Graphite is the primary raw material used to create graphene oxide. However, other biomass sources can also be used to create or combine the carbon source. Seaweed (Sargassum sp.), which has a decent carbon content, was used in this study as the biomass used as a carbon source for mixing. The objective of this research is to ensure how adding seaweed charcoal will affect the electrical characteristics of graphene oxide. The modified Hummer process was used to create the materials. There are four different compositions available: pure graphite (100%), 70:30 (graphite and seaweed), 60:40 (graphite and seaweed), and 50:50 (graphite and seaweed). The product of graphene oxide variations made from other compositions will be compared to those of 100% graphite composition. The result demonstrated that the addition of seaweed charcoal to the graphene oxide synthesis was successful. It can be seen from some of the characteristics of graphene oxide at an angle of 2Ɵ by XRD testing. In the FTIR test, it was discovered that the graphene oxide sample contained C-O, C=O, C=C, and O-H functional groups, and in the SEM test, peeling was discovered on the sample surface as a result of the oxidation process. The addition of seaweed charcoal with pure graphite synthesized by the modified Hummers method affects the electrical properties of the resulting graphene oxide. The material's conductivity value and the area capacitance value of the graphene oxide material both drop in the LCR Meter characterization instrument.